Brain calcification process and phenotypes according to age and sex: Lessons from SLC20A2, PDGFB, and PDGFRB mutation carriers. Issue 7 (30th June 2015) - Nicolas, Gaël; Charbonnier, Camille; de Lemos, Roberta Rodrigues; Richard, Anne‐Claire; Guillin, Olivier; Wallon, David; Legati, Andrea; Geschwind, Daniel; Coppola, Giovanni; Frebourg, Thierry; Campion, Dominique; de Oliveira, João Ricardo Mendes; et al.
Abstract : Primary Familial Brain Calcification (PFBC) is a dominantly inherited cerebral microvascular calcifying disorder with diverse neuropsychiatric expression. Three causative genes have been identified: SLC20A2, PDGFRB and, recently, PDGFB, whose associated phenotype has not yet been extensively studied. We included in the largest published case series of genetically confirmed PFBC, 19 PDGFB (including three new mutations), 24 SLC20A2 (including 4 new mutations), and 14 PDGFRB mutation carriers, from two countries (France and Brazil). We studied clinical features and applied our visual rating scale on all 49 available CT scans. Among the symptomatic mutation carriers (33/57, 58%), the three most frequently observed categories of clinical features were psychiatric signs (72.7%, 76.5%, and 80% for PDGFB, SLC20A2, and PDGFRB, respectively), movement disorders (45.5%, 76.5%, and 40%), and cognitive impairment (54.6%, 64.7%, and 40%). The median age of clinical onset was 31 years, 25% had an early onset (before 18) and 25% a later onset (after 53). Patients with an early clinical onset exhibited mostly isolated psychiatric or cognitive signs, while patients with a later onset exhibited mostly movement disorders, especially in association with other clinical features. CT scans rating allowed identifying four patterns of calcification. The total calcification score was best predicted by the combined effects of gene ( SLC20A2 > PDGFB > PDGFRB mutations), sex (male), and (increasing) age, defining three risk classes, which correlated with the four patterns of calcification. These calcification patterns could reflect the natural history of the calcifying process, with distinct risk classes characterized by different age at onset or rate of progression. © 2015 Wiley Periodicals, Inc.